The effect of competition level on penalties and injuries in youth soccer - Walsh, S.; Walden, N.; Hunt, T. (The Sport Journal, 2020)
There are an estimated 3 million youth soccer participants in the United States. As concern rises for the safety of youth athletes, organizations are changing the rules to make the game safer, potentially resulting in more penalized behaviors. Differences in competition levels may contribute to varying numbers of fouls and injuries. PURPOSE: Examine the effect of competition level on the number of fouls and injuries in youth soccer. METHODS: During the competitive season, two soccer organizations were observed to examine behaviors associated with sportsmanship, fouls, and injuries during a game situation. The organizations consisted of teams from a recreation department and a travel academy soccer club located in South Georgia. Teams consisted of male and female athletes ranging from 6-16 years old, whom were divided by pre-determined age groups within the leagues. Observational data was collected on game statistics which included spectator, coach and athlete behavior, as well as fouls and injuries, within the soccer organizations. A total of 86 recreational (n=52) and club (n=34) games were observed. RESULTS: Club soccer teams had a greater number of fouls (n=224, mean ± SD 1.22 ± 1.28, ranging from 0-18) compared to recreational teams (n=61, mean ± SD 1.22 ± 1.28, ranging from 0-5). The number of injuries were not affected by the level of competition in club (n= 26; 0.76 + 0.99, ranging from 0-3 per game) and recreation (n=27; mean ± SD 0.53 ± 0.83, ranging from 0-3) youth soccer teams. CONCLUSION: This pilot study provides preliminary evidence that competition level may be the driving force of behaviors that lead to penalties. Regardless of the number of penalties for both organizations, the number of injuries were minuscule; thus, severing the link between aggressive behaviors and injury in youth soccer. Therefore, it seems that a greater level of competition in youth soccer leads to more fouls, but not more injuries. Future research should consider situational factors that may impact these findings such as coaches and parent`s behaviors throughout the game.